The Evaluation of Rationality of Medicines Use in Terms of Prescribing Indicators At The Health Center (Puskesmas) Serdang Bedagai District In 2019 - Sasmita, Irawati; K, Khairunnisa; Aminah, Dalimunthe (Asian Journal of Pharmaceutical Research and Development, 2021)
Objective: The aim of this study was to determine the effectiveness of aloe vera gel in inhibiting skin aging. Method: The powder was extracted with ethanol in macerated method. Extract ethanol were analyzed for antioxidant activity with DPPH assay. Aloe vera extract that has been obtained then made variations of different extract concentrations namely 3% and 6% based on the orientation of researchers to determine the concentration, then in the formulation into gel. Anti-aging activity testing using skin analyzer tools with moisture parameters, collagen levels, pore, sensitivity before and after exposure to UV A and UV B rays. Results: IC50 value of aloe vera extract obtained by 138.65 ppm. Based on the classification of antioxidant activity shows that IC50 value of aloe vera extract has moderate antioxidants that range from 101 to 250 ppm. The percentage of moisture content in week I to week IV, F3 has an increase of 26% i.e week 1 is 4% and week IV is 30%. The percentage of collagen levels in week I to week IV, F3 has an increase of 50% i.e week 1 is 30% and week IV is 80%. Increase in the percentage of elasticity in the week I to week IV. F3 had the highest increase of 25%, in week 1 it was 50% and week IV was 75%. A large decrease in pores occurs in weeks I through week IV. F3 had the highest decrease of 0.06 mm, in the week I was 0.07 mm and week IV was 0.01 mm. Conclusion: Aloe vera extract gel preparation has activity as a rejuvenation agent at a concentration of 6%.